An introduction to applied professional research for accountants /cDavid A. Ziebart ; contributing authors, Anita L. Feller, Karen H. Molloy, Thomas C. Omer - Ziebart, David Allen (Prentice Hall, 1998)
Describes the applied professional research process with applications in financial reporting and auditing. The text explains how to use Internet resources for conducting applied professional research. The casebook component contains accouting and reporting cases